The Princess's Bow alias Bow Begum. - Sayers, James, 1748-1823 (Cornell, Thomas, 1788)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Burke, Edmund, 1729-1797; Fox, Charles James, 1749-1806; Francis, Philip, Sir, 1740-1818; Sheridan, Richard Brinsley, 1751-1816; Great Britain -- Politics and government -- 1760-1820 -- Caricatures and cartoons